Microbial hydrogen oxidation potential in seasonally hypoxic Baltic Sea sediments - Adam-Beyer, Nicole; Deusner, Christian; Schmidt, Mark; Perner, Mirjam (Frontiers in Microbiology, 2025)
The majority of the organic matter (OM) degradation on the seafloor occurs in coastal regions. Since oxygen (O2) becomes quickly depleted in the top sediments, most of the OM decomposition is driven by microbial sulfate reduction (SR) and fermentation, the latter generating molecular hydrogen (H2). If the H2 is not consumed by hydrogenotrophic microorganisms and accumulates in the sedimentary porewaters, OM degradation is hindered. Despite the importance of H2 scavenging microorganisms for OM mineralization, the knowledge on H2 oxidizers and their constraints in coastal marine sediments is still quite limited. Here we investigated the role of H2 oxidizers in top (2 to 5 cm, suboxic-sulfidic) and bottom (18 to 22 cm, sulfidic) coastal sediments from a location exposed to seasonal hypoxia in the SW Baltic Sea. We used sediments from April, May and August, representative of different seasons. We spiked respective sediment slurries with H2 and incubated them for up to 4 weeks under O2-free conditions. H2 consumption potential, methane production and shifts in bacterial and archaeal 16S rRNA gene amplicons (generated from RNA) were assessed over time. The seasonal variations in sedimentary community compositions and pore water geochemistry already gave distinct starting conditions for the H2 enrichments. Sediments exposed to near anoxic bottom water conditions favored a microbial starter community exhibiting the highest H2 oxidation potential. Most of the observed H2 oxidation potential appeared associated with hydrogenotrophic sulfate reducers. The putative involvement of massively enriched ANME in H2 cycling in May 18 to 22 cm sediment horizons is conspicuous. While the differences in the observed H2 oxidation potentials in the studied sediment slurries are likely related to the (season-depending) overall redox state of the sediments and interstitial waters, the influence of microbial interconnections could not be fully resolved and evaluated, demonstrating the need for further consumption- and community-based studies.